2022
DOI: 10.1007/s00296-022-05101-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided genicular nerve block versus physical therapy for chronic knee osteoarthritis: a prospective randomised study

Abstract: To compare the effectiveness of ultrasound-guided genicular nerve block (GNB) and physical therapy (PT) in patients with chronic knee osteoarthritis. A prospective randomised study with 102 patients (45-70 years) was performed wherein the patients received ultrasound-guided GNB (n = 51) and PT (n = 51) along with a standard home exercise programme. Scores for pain on a Visual Analogue Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and 6-min walking test (6MWT) were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Improvement in pain severity as measured by NRS and functionality as assessed by WOMAC was demonstrated at a 3-month follow-up (22). Guler et al (23) showed that ultrasound-guided genicular nerve blockade with a total mixture of 5 ml of 2% lidocaine and 40 mg of triamcinolone, to patients with knee osteoarthritis has sustained improvement in pain, physical function, and physical capacity for up to 12 weeks. Fonkoue et al (24) performed a single session genicular nerve blockade with a mixture of lidocaine and triamcinolone, using scopy-controlled classic and revised target techniques, to patients with chronic knee pain due to osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in pain severity as measured by NRS and functionality as assessed by WOMAC was demonstrated at a 3-month follow-up (22). Guler et al (23) showed that ultrasound-guided genicular nerve blockade with a total mixture of 5 ml of 2% lidocaine and 40 mg of triamcinolone, to patients with knee osteoarthritis has sustained improvement in pain, physical function, and physical capacity for up to 12 weeks. Fonkoue et al (24) performed a single session genicular nerve blockade with a mixture of lidocaine and triamcinolone, using scopy-controlled classic and revised target techniques, to patients with chronic knee pain due to osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding the safety and bottlenecking of drug treatments have increased the focus on non-drug therapies. Non-drug treatments for KOA have the advantages of significantly higher efficacy, lasting effects, and few adverse reactions, and have become a hot research topic in recent years ( 11 , 12 ). Several guidelines and consensuses ( 13 – 15 ) list non-drug therapies as recommended interventions for the clinical treatment of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches prevailing for targeting this nerve. Conventionally, the bony cortex near the corresponding artery at the shaft and medial epicondyle junction is used as the landmark for targeting this nerve [ 24 , 35 – 39 ]. The junction of the shaft and medial epicondyle of the femur in the coronal plane and half of the depth of the femur in the axial view is also used [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 , 45 ] Even though there is variation in origin, the distal course is constant [ 41 ]. Conventionally, the nerve is targeted at the bony cortex, near the corresponding artery, over the junction of the shaft and lateral femoral epicondyle [ 24 , 35 – 39 , 42 , 44 ]. Recently described techniques include, targeting the superolateral popliteal fossa, medial to biceps femoris tendon, around 2.6 cm proximal to the most prominent part of the lateral femoral epicondyle visualized under ultrasound [ 46 ], or locating the junction of the shaft and lateral epicondyle of the femur in the coronal plane and to target either half of the depth of femur in axial view [ 32 , 40 ] or the crest separating lateral and posterior cortex, in axial view [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation